Passing for Black : the life and careers of Mae Street Kidd - Kidd, Mae Street, 1904-1999 (University Press of Kentucky, 1997)
In 1976, Kentucky state legislator Mae Street Kidd successfully sponsored a resolution ratifying the 13th, 14th, and 15th amendments to the U.S. Constitution. It was fitting that a black woman should initiate the state's formal repudiation of slavery; that it was Mrs. Kidd was all the more appropriate. Born in Millersburg, Kentucky, in 1904 to a black mother and a white father, Mae grew up to be a striking woman with fair skin and light hair. Sometimes accused of trying to pass for white in a segregated society, Mae felt that she was doing the opposite - choosing to assert her black identity. Passing for Black is her story, in her own words, of how she lived in this racial limbo and the obstacles it presented. As a Kentucky woman of color during a pioneering period of minority and women's rights, Mae Street Kidd seized every opportunity to get ahead. She attended a black boarding academy after high school and went on to become a successful businesswoman in the insurance and cosmetic industries in a time when few women, black or white, were able to compete in a male-dominated society. She also served with the American Red Cross in England during World War II. It was not until she was in her sixties that she turned to politics, sitting for seventeen years in the Kentucky General Assembly, where she crusaded vigorously for housing rights.